INFORMATION AND KNOWLEDGE IN THE PROCESS OF TRANSFORMATION OF MODERN CULTURE - Трач, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Basic looks are analysed to functioning of information and knowledge in informative society as society of knowledges, a role and value of information and knowledges is exposed in cultural development.